Fabrication and Evaluation of Floating Zidovudine Microbeads for Prolonged Kinetic Release and Bioavailability - Dobhal, Kiran; Verma, Shalu; Singh, Alka; Kukreti, Gauree (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim AIDS (Acquired Immuno Deficiency Syndrome) is one of the most sexually transmitted diseases with chronic depletion of immunity in the body associated with social stigma, social isolation and depression. Zidovudine is an orally prescribed antiretroviral drug for AIDS.The current work’s objective was to develop floating microbeads of zidovudine to achieve sustained release action. Floating microbeads are a non-effervescent, gastro-retentive drug delivery technology that has been designed to lengthen the gastric residence time of dosage forms. Materials and Methods The ionotropic gelatin method has opted for the development of Zidovudine floating microbeads. Different ratio of used polymers affects the buoyancy, drug release, particle size, drug entrapment, density, and in vitro drug release of microbeads. Calcium chloride was used as a cross linker and Glyceryl monostearate was used as a disaggregating agent. Results The resultant microbeads were furthermore evaluated by FT-IR, SEM, Micrometric, Density, drug entrapment efficiency, buoyancy and in vitro drug release and cumulative drug release studies. Conclusion The microbeads were found to be spherical; the mean particle size was estimated to be 594 ± 7.46 μm with maximum drug entrapment efficiency of 82.30 ± 1.63% w/w. The in vitro percentage release of the drug after 12 hr of the formulation MB3 showed the highest drug release which was found to be 90.05 ± 0.64. SEM images showed smooth and spherical shapes.
Keywords: Microbeads; Sustained; Zidovudine; Floating; Gastro-retentive